Globalization and the health and well-being of migrant domestic workers in Malaysia - Spitzer, Denise L.; Thambiah, Shanthi; Wong, Yut L.; Kaundan, Manimaran K. (Université d'Ottawa | University of Ottawa, 2023)
Abstract Background Neoliberal globalization contributes to the out-migration of labour from sending countries in the global South. Supported by multilateral organizations including the IMF and World Bank, the migration and development nexus holds that nations and households in migrant sending countries can migrate their way out of poverty. Two countries that embrace this paradigm, the Philippines and Indonesia, are major suppliers of migrant labour including domestic workers, and Malaysia is a primary destination country. Theory and methods We deployed a multi-scalar and intersectional lens to highlight the impact of global forces and policies, interacting with constructions of gender and national identity, to explore the health and wellbeing of migrant domestic workers in Malaysia. In addition to documentary analysis, we conducted face-to-face interviews with 30 Indonesian and 24 Filipino migrant domestic workers, five representatives from civil society organizations, three government representatives, and four individuals engaged in labour brokerage and the health screening of migrant workers in Kuala Lumpur. Results Migrant domestic workers in Malaysia work long hours in private homes and are not protected by labour laws. Workers were generally satisfied with their access to health services; however, their intersectional status, which is both an outcome of, and contextualized by, the lack of opportunities in their own country, prolonged familial separation, low wages, and lack of control in the workplace, contributed to stress and related disorders—which we regard as the embodied manifestation of their migratory experiences. Migrant domestic workers eased these ill effects through self-care, spiritual practices, and the embrace of gendered values of self-sacrifice for the family as a form of solace. Conclusions Structural inequities and the mobilization of gendered values of self-abnegation underpin the migration of domestic workers as a development strategy. While individual self-care practices were used to cope with the hardships of their work and family separation, these efforts did not remedy the harms nor redress structural inequities wrought by neoliberal globalization. Improvements in the long-term health and wellbeing of Indonesian and Filipino migrant domestic workers in Malaysia cannot focus solely on the preparation and maintenance of healthy bodies for productive labour, but must attend to workers’ attainment of adequate social determinants of health, which challenges the migration as development paradigm. Neo-liberal policy instruments such as privatization, marketisation and commercialization of migrant labour have led to both host and home countries benefitting, but at the expense of the migrant domestic workers’ well-being.